CONCEPTUAL ANALYSIS OF SUSTAINABLE TOURISM MANAGEMENT IN INDONESIA - Cherryl Elshinta Hadi; Riko Reinarto; Raden Aswin Rahadi, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Indonesian Tourism Industry was targeted as the second source of foreign exchange, but the negative impact from this industry has become an issue that needs to be resolved. The concept of tourism management in Indonesia is still outmoded due to focusing on the massive exploitation of resources for current needs instead of optimizing the resources for the future, certainly, this problem will be a threat for Indonesia's tourism industry continuance in the future. From the socio-cultural impact, economic impact, and environmental impact, altogether has some negative impact that was caused by the industry. The issue not only comes from the tourism producers but also the tourists. In this study, the authors explore the conceptual analysis of sustainable tourism management in Indonesia. Using literature synthesis, it is expected to produce a conceptual model for sustainable tourism management in Indonesia. Based on the literature review, we can conclude that there are three pillars of sustainability that need to be addressed: socio-cultural, economic, and environmental. Future research can be explored through qualitative and quantitative approaches to understand more about the effects of those three pillars in developing sustainable tourism in Indonesia.